Synergistic Association With Root Endophytic Fungi Improves Morpho-Physiological and Biochemical Responses of Chenopodium quinoa to Salt Stress - González-Teuber, Marcia; Contreras, Rodrigo A.; Zúñiga, Gustavo E.; Barrera, Diego; Bascuñán-Godoy, Luisa (Frontiers in Ecology and Evolution, 2022)
Symbiotic associations with microbes can contribute to mitigating abiotic environmental stress in plants. In this study, we investigated individual and interactive effects of two root endophytic fungal species on physiological and biochemical mechanisms of the crop Chenopodium quinoa in response to salinity. Fungal endophytes Talaromyces minioluteus and Penicillium murcianum, isolated from quinoa plants that occur naturally in the Atacama Desert, were used for endophyte inoculation. A greenhouse experiment was developed using four plant groups: 1) plants inoculated with T. minioluteus (E1+), 2) plants inoculated with P. murcianum (E2+), 3) plants inoculated with both fungal species (E1E2+), and 4) non-inoculated plants (E-). Plants from each group were then assigned to either salt (300 mM) or control (no salt) treatments. Differences in morphological traits, photosynthesis, stomatal conductance, transpiration, superoxide dismutase (SOD), ascorbate peroxidase (APX), peroxidase, (POD), phenylalanine ammonia-lyase (PAL), phenolic content, and lipid peroxidation between plant groups under each treatment were examined. We found that both endophyte species significantly improved morphological and physiological traits, including plant height, number of shoots, photosynthesis, stomatal conductance, and transpiration, in C. quinoa in response to salt, but optimal physiological responses were observed in E1E2+ plants. Under saline conditions, endophyte inoculation improved SOD, APX, and POD activity by over 50%, and phenolic content by approximately 30%, with optimal enzymatic responses again observed in E1E2+ plants. Lipid peroxidation was significantly lower in inoculated plants than in non-inoculated plants. Results demonstrate that both endophyte species enhanced the ability of C. quinoa to cope with salt stress by improving antioxidative enzyme and non-enzyme systems. In general, both FE species interacting in tandem yielded better morphological, physiological, and biochemical responses to salinity in quinoa than inoculation by a single species in isolation. Our study highlights the importance of stress-adapted FE as a biological agent for mitigating abiotic stress in crop plants.